Biodiesel production from waste frying oil using waste animal bone and solar heat. (January 2016) - Corro, Grisel; Sánchez, Nallely; Pal, Umapada; Bañuelos, Fortino
Graphical abstract: Highlights: Biodiesel production from waste frying oil (WFO) using solar radiation as heating source. Free fatty acids (FFAs) of WFO could be esterified using calcined waste animal-bone catalyst. Produced biodiesel fulfills all the international requirements for its utilization as a fuel. Mechanism for FFA esterification is proposed considering Ca3 (PO4 )3 OH at catalyst surface. Biodiesel produced through this process is sustainable and of low cost. Abstract: A two-step catalytic process for the production of biodiesel from waste frying oil (WFO) at low cost, utilizing waste animal-bone as catalyst and solar radiation as heat source is reported in this work. In the first step, the free fatty acids (FFA) in WFO were esterified with methanol by a catalytic process using calcined waste animal-bone as catalyst, which remains active even after 10 esterification runs. The trans-esterification step was catalyzed by NaOH through thermal activation process. Produced biodiesel fulfills all the international requirements for its utilization as a fuel. A probable reaction mechanism for the esterification process is proposed considering the presence of hydroxyapatite at the surface of calcined animal bones.